THE APPLICATION OF SELF-REFLECTION IN THE PROBLEM-BASED LEARNING MODEL TO DEVELOP STUDENTS' CRITICAL THINKING SKILLS: A SYSTEMATIC LITERATURE REVIEW - Audila, Rahma; Yusuf, Rinaldi (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This study systematically investigates the integration of self-reflection within the Problem-Based Learning (PBL) model and its impact on enhancing critical thinking skills among elementary school students. Employing a Systematic Literature Review (SLR) guided by the PRISMA protocol, 20 articles were retrieved from reputable databases including Google Scholar, SINTA, DOAJ, Garuda, and ResearchGate. The selection process comprised five stages: identification, initial screening, eligibility assessment, methodological quality evaluation, and final inclusion. Only five studies met all criteria, focusing on PBL with embedded self-reflection at the elementary level, presenting empirical evidence, and examining critical thinking as the primary outcome. Findings reveal that incorporating structured self-reflection into PBL fosters active student engagement, deepens conceptual understanding, and cultivates metacognitive awareness key foundations of critical thinking. Moreover, self-reflection enables learners to assess their cognitive processes, refine learning strategies, and link experiences to targeted learning objectives. This review recommends that educators embed reflective practices within PBL designs to promote critical, autonomous learners equipped for the demands of 21st-century education.